2013
DOI: 10.1002/pssa.201228786
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magnetic properties of Er‐doped SnO2 nanoparticles

Abstract: Er-doped SnO 2 nanoparticles were synthesized with varying Er concentration by a sol-gel method. X-ray diffraction (XRD) and high-resolution transmission electron microscopic studies reveal the crystalline nature of the nanoparticles and the crystallite size decreases with the increase of Er concentration in SnO 2 . For higher Er concentration, the evolution of Er 2 O 3 as a secondary phase is detected. The X-ray photoelectron spectroscopy (XPS) study depicts the existence of 4d level of Er along with a partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The authors reported an increase of the lattice parameters by Pr 3+ doping of SnO 2 NPs (0x10%). Sambasivam et al and Bhaumik et al observed an antiferromagnetic behavior with increasing Er content in SnO 2 NPs which could be explained by the magnetization M in Pr and Er doped TiO 2 and SnO 2 NPs.…”
Section: Numerical Results and Discussionmentioning
confidence: 94%
“…The authors reported an increase of the lattice parameters by Pr 3+ doping of SnO 2 NPs (0x10%). Sambasivam et al and Bhaumik et al observed an antiferromagnetic behavior with increasing Er content in SnO 2 NPs which could be explained by the magnetization M in Pr and Er doped TiO 2 and SnO 2 NPs.…”
Section: Numerical Results and Discussionmentioning
confidence: 94%
“…To prepare the target for laser ablation, we had used Mn 0.02 Sn 0.98 O 2 nanoparticles, prepared by simple sol-gel technique. 25,26 Those nanoparticles were pressurized to make pellet of 1 inch diameter for PLD target. Before deposition, PLD chamber was pumped with a base pressure of 10 À5 millibar.…”
Section: Methodsmentioning
confidence: 99%